DESIGN OF YASMIN FARM DAIRY CATTLE FARMING AREA IN PURWOREJO - Maksum, Rizal; Hermanto, Heri; Hermawan, Hermawan (Clean Energy and Smart Technology, 2025)
This study proposes the design of an integrated dairy farming area at Yasmin Farm, Purworejo, to optimize land use, safeguard animal welfare, and enhance operational efficiency. A mixed qualitative–quantitative design approach was adopted, combining literature review, comparative case observations of reference farms, on-site surveys, and a space-requirement analysis that informed the layout of barns, milking facilities, feed storage, and waste-handling units. The planning embeds green-design strategies—natural ventilation and daylighting, water harvesting, resource-efficient circulation, and staged waste valorization (composting/biogas)—alongside appropriate automation for herd monitoring and milking. The resulting scheme organizes the estate into clear functional zones (production, support, education–tourism, and utilities) to minimize cross-contamination risk, shorten process flows, and improve worker safety. Expected benefits include more stable milk quality and capacity, reduced environmental footprint, and opportunities for education and community engagement. The work’s novelty lies in a context-specific, medium-scale dairy farm blueprint that couples spatial programming with sustainability and edutourism functions, offering a practical model for Central Java and similar tropical settings.